Organizational excellence and its relationship to administrative empowerment of sports activity departments in the central region from the point of view of technical supervisors. (Damu Journal of Sport Sciences, 2025)
This study aimed to know the relationship between organizational excellence and administrative empowerment of sports activity departments in the central region from the point of view of technical supervisors, as well as to identify the problems and obstacles facing technical supervisors in the central region. The research community was identified from technical supervisors in sports activity departments in the central region in Iraq, which includes (Baghdad, Anbar, Salah al-Din, Diyala and Kut). The number of the research community reached (187) technical supervisors distributed over five governorates. The number of valid questionnaires reached (187) questionnaires, which represents (100%) of the research community.The researchers concluded that there is a correlation between organizational excellence and administrative empowerment, and that the success of this relationship depends on the efficiency and performance of the managers of the sports and scouting activity departments with the technical supervisors, and the integration of their experiences and work to improve and develop the infrastructure of the sports and scouting activity departments. The researchers recommended holding training and educational courses and workshops that contribute to developing and strengthening the administrative and technical work aspect, as well as working to provide the necessary financial allocations within the sports and scouting activity departments and giving importance and continuous support from the Ministry of Education and the Activity Directorate to the technical supervisor for his ability to advance the reality of the sports and scouting activity departments.